THE COMPARATIVE ANALYSIS OF LEARNING OUTCOMES USING NORM-REFERENCED TEST (NRT) AND CRITERION-REFERENCED TEST (CRT) IN THE SUBJECT OF ISLAMIC EDUCATION - Herman Darmawan (Tarbiyah Islamiyah)
To measure whether test participants have successfully completed the test given by the examiner or not, an assessment technique or approach is required. In this case, an examiner can use two types of assessments, namely norm-referenced assessment and criterion-referenced assessment. Most of the teachers who teach Islamic Religious Education at SDN 5 Syamsudin Noor Banjarbaru only use criterion-referenced assessment. Therefore, this research is conducted to help explain both approaches while providing practical analysis using Microsoft Excel or manual calculations. This research uses a qualitative method with a descriptive-quantitative approach, where the data is obtained from the field, using documentation as the data collection technique. The results of this study show that the achievement of Class 1 A students at SDN 5 Syamsudin Noor in the Midterm Assessment (PTS) revealed that when using the Norm-Referenced Assessment with manual calculations in the subject of Islamic Religious Education, 13 out of 25 students were declared not to have passed. Meanwhile, when using the criterion-referenced approach model, in manual calculations for the Islamic Religious Education grades, with the passing grade set at 75, it was found that 8 students were declared not to have passed.